DETERMINAN PERTUMBUHAN EKONOMI DI PROVINSI SUMATERA SELATAN: PERKEBUNAN KARET, INFRASTRUKTUR, DAN PENDUDUK USIA PRODUKTIF - Sari, Emilda; Indrayanti, Wiwin (Salam (Islamic Economics Journal), 2026)
This study investigates the influence of rubber plantation production, road and electricity infrastructure, and the productive age population on the economic growth of regencies/cities in South Sumatra Province. The analysis employs panel data regression using data from 17 regencies/cities over the 2015–2024 period, with the Random Effect Model (REM) identified as the most appropriate estimation technique. The empirical findings reveal that road and electricity infrastructure exert a positive and significant impact on economic growth. In contrast, rubber plantation production and the productive age population show a negative yet insignificant effect. These results underscore the strategic role of infrastructure development in supporting economic performance and accelerating regional development. Therefore, strengthening investment in road and electricity infrastructure is recommended as a priority policy direction for local governments in South Sumatra.   Keywords : Economic Growth, Plantation, Infrastructure, Productive Age